Signal Pathway of Estrogen and Estrogen Receptor in the Development of Thyroid Cancer - Liu, Jian; Xu, Tianmin; Ma, Li; Chang, Weiqin (Frontiers in Oncology, 2021)
The molecular mechanisms underlying the development of thyroid cancer (TC) have been examined through extensive experiments. A large number of studies have shown that the incidences of thyroid cancer in women is much higher than that in men, so estrogen plays a key role in the development of thyroid cancer. Estrogen plays its growth-promoting role through classical genomic and non-genomic pathways mediated by membrane-bound estrogen receptors. It also can affect tumor progression by regulating the tumor microenvironment. We summarize the understanding of molecular mechanisms of estrogen signaling pathways in thyroid cancer. Furthermore, it will provide a new target for the treatment of thyroid carcinoma by blocking estrogen and its related action pathway.